Shark nanobodies with potent SARS-CoV-2 neutralizing activity and broad sarbecovirus reactivity - Chen, Wei-Hung; Hajduczki, Agnes; Martinez, Elizabeth J.; Bai, Hongjun; Matz, Hanover; Hill, Thomas M.; Lewitus, Eric; Chang, William C.; Dawit, Layla; Peterson, Caroline E.; Rees, Phyllis A.; Ajayi, Adelola B.; et al. (Nature communications, 2023)
Despite rapid and ongoing vaccine and therapeutic development, SARS-CoV-2 continues to evolve and evade, presenting a need for next-generation diverse therapeutic modalities. Here we show that nurse sharks immunized with SARS-CoV-2 recombinant receptor binding domain (RBD), RBD-ferritin (RFN), or spike protein ferritin nanoparticle (SpFN) immunogens elicit a set of new antigen receptor antibody (IgNAR) molecules that target two non-overlapping conserved epitopes on the spike RBD. Representative shark antibody variable NAR-Fc chimeras (ShAbs) targeting either of the two epitopes mediate cell-effector functions, with high affinity to all SARS-CoV-2 viral variants of concern, including the divergent Omicron strains. The ShAbs potently cross-neutralize SARS-CoV-2 WA-1, Alpha, Beta, Delta, Omicron BA.1 and BA.5, and SARS-CoV-1 pseudoviruses, and confer protection against SARS-CoV-2 challenge in the K18-hACE2 transgenic mouse model. Structural definition of the RBD-ShAb01-ShAb02 complex enabled design and production of multi-specific nanobodies with enhanced neutralization capacity, and picomolar affinity to divergent sarbecovirus clade 1a, 1b and 2 RBD molecules. These shark nanobodies represent potent immunotherapeutics both for current use, and future sarbecovirus pandemic preparation. SARS-CoV-2 variants of concern continue to emerge, reducing vaccine efficacy and limiting therapeutic options. Here, Chen and colleagues describe the identification and design of shark nanobodies with pansarbecovirus activity.